I, Alex Cross - Patterson, James (New York : Vision, 2010)
Determined to capture the psychopath responsible for murdering his niece, Alex Cross discovers that the young woman was among a dangerous group of people and was not the only one to have disappeared.
Originally published: New York : Little, Brown, 2009.
Keywords: African American detectives -- Fiction; Murder -- Fiction